Impact of cyclic water stress on growth, physiological responses and yield of rice (Oryza sativa L.) grown in tropical environment - Mohd Zain, Nurul Amalina; Ismail, Mohd Razi; Puteh, Adam; Mahmood, Maziah; Islam, Md Robiul (Universidade Federal de Santa Maria, 2014)
A series of water stress cycles [5, 10, 15, 20, 25 and 30 days of irrigation intervel including control flooded (CF), control saturated (CS)] were exposed to investigate the impact of cyclic water stress on growth, physiological responses and yield of a famous Malaysian rice variety, MR220. The study also aimed to determine optimum irrigation schedule for better production of rice. It was observed that grain yield, total biomass, filled spikelet, 1000 grain weight, total panicle, tillers mortality, plant height and number of tillers per plant reduces with increased duration of water stress cycles. Grain yield was higher both in CF and CS condition and those are statistically identical to 5 days of stress cycle or irrigation intervel. The present experiment shows that growth performance and physiological activities of rice differ marginally for 5 days of irrigation difference, exceding that time would reduce yield significantly. The study also showed that proline accumulation and malondialdehyde (MDA) contents in levels increased with increasing duration of water stress cycle. Depending on the findings of the present, it can be stated that rice variety MR220 do not require flooding irrigation and irrigation cycle of 5 days interval is more apprapriate to increase water use and higher yield of rice.